Web and Mobile Application Development with QR Code Features for Digital Payments and Donations in Churches - Albertus Agung Kusuma; Wahyu Sri Utami (SAFE-Network, 2026)
The expansion in information technology has created opportunities for religious groups. institutions to enhance the oversight of the administration and distribution of information, this study has the aim of developing an application that uses a web platform. and mobile as a means of information and digitization of administration at the Sumbawa Parish Church of the Redeemer. This application was developed to facilitate the management of church member data, service schedules, sacraments, and various church announcements digitally and integrated. The methods applied include needs assessment, system architecture, execution, testing, and software upkeep. The outcomes of the development demonstrate that this the initiative can improve the efficiency of management tasks and lower the use of physical documents, and make it easier for congregations to get the latest information in real-time. With the presence of this program is designed to make church administration more organized, straightforward, and can improve communication between the church and the congregation.